International Journal of Clinical Oncology - Ogawa, Osamu; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
The International Journal of Clinical Oncology (IJCO) welcomes original research papers on all aspects of clinical oncology that report the results of novel and timely investigations. Reports on clinical trials are encouraged. Experimental studies will also be accepted if they have obvious relevance to clinical oncology. Membership in the Japan Society of Clinical Oncology is not a prerequisite for submission to the journal. Papers are received on the understanding that: their contents have not been published in whole or in part elsewhere; that they are subject to peer review by at least two referees and the Editors, and to editorial revision of the language and contents; and that the Editors are responsible for their acceptance, rejection, and order of publication.
Keywords: Cancer research; Oncology; Surgical oncology; Oncology; Surgical Oncology; Cancer Research